2023
DOI: 10.1249/esm.0000000000000004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of an Acute Bout of Aerobic or Resistance Exercise on Nonexercise Physical Activity

Abstract: Introduction/Purpose A reduction in nonexercise physical activity (NEPA) after exercise may reduce the effectiveness of exercise interventions on weight loss in adults with overweight or obesity. Aerobic exercise (AEx) and resistance exercise (REx) may have different effects on NEPA. The purpose of this secondary analysis was to examine the effect of a single bout of AEx or REx on NEPA and sedentary behavior in inactive adults with overweight or obesity. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Among the various physical activity categories, such as aerobic exercise, strength exercise, flexibility training, and light walking, engaging in aerobic exercise is suggested to have behavioral and cardiorespiratory benefits [38]. Furthermore, a previous study found that engaging in aerobic or resistance exercise did not reduce non-exercise physical activity after the exercise [39].…”
Section: Discussionmentioning
confidence: 99%
“…Among the various physical activity categories, such as aerobic exercise, strength exercise, flexibility training, and light walking, engaging in aerobic exercise is suggested to have behavioral and cardiorespiratory benefits [38]. Furthermore, a previous study found that engaging in aerobic or resistance exercise did not reduce non-exercise physical activity after the exercise [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, human studies face difficulties in accurately and continuously detecting NEPA and core body temperature as indicators of whole-body thermogenesis after exercise (28,29). Indeed, compensatory responses in NEPA to exercise intervention often exhibit considerable variability among participants due to challenges in controlling external factors such as genetic and social background, living conditions, dietary habits, and other free-living activities (30,31). In addition, ingestible telemetric capsules are often used for the measurement of core body temperature in free-living humans (32), but accurate detection could fail owing to the influence of some foods/drinks (29).…”
Section: Introductionmentioning
confidence: 99%